Cationic Functionalisation by Phosphenium Ion Insertion. Issue 71 (23rd November 2020) - Riesinger, Christoph; Dütsch, Luis; Balázs, Gábor; Bodensteiner, Michael; Scheer, Manfred
Abstract: The reaction of [Cp′′′Ni(η 3 ‐P3 )] (1 ) with in situ generated phosphenium ions [RR′P] + yields the unprecedented polyphosphorus cations of the type [Cp′′′Ni(η 3 ‐P4 R2 )][X] (R=Ph (2 a ), Mes (2 b ), Cy (2 c ), 2, 2′‐biphen (2 d ), Me (2 e ); [X] − =[OTf] −, [SbF6 ] −, [GaCl4 ] −, [BAr F ] −, [TEF] − ) and [Cp′′′Ni(η 3 ‐P4 RCl)][TEF] (R=Ph (2 f ), t Bu (2 g )). In the reaction of 1 with [Br2 P] +, an analogous compound is observed only as an intermediate and the final product is an unexpected dinuclear complex [{Cp′′′Ni}2 (μ, η 3 :η 1 :η 1 ‐P4 Br3 )][TEF] (3 a ). A similar product [{Cp′′′Ni}2 (μ, η 3 :η 1 :η 1 ‐P4 (2, 2′‐biphen)Cl)][GaCl4 ] (3 b ) is obtained, when 2 d [GaCl4 ] is kept in solution for prolonged times. Although the central structural motif of 2 a –g consists of a "butterfly‐like" folded P4 ring attached to a Cp′′′Ni fragment, the structures of 3 a and 3 b exhibit a unique asymmetrically substituted and distorted P4 chain stabilised by two Cp′′′Ni fragments. Additional DFT calculations shed light on the reaction pathway for the formation of 2 a –2 g and the bonding situation in 3 a . Abstract : Rings and chains with P : The reaction of [Cp′′′Ni(η 3 ‐P3 )] with in situ generated phosphenium cations [R2 P] + yields unprecedented cationic bent P4 R2 rings and P4 R3 chains coordinated to Cp′′′Ni fragments. These results suggest that the formation of polyphosphorus cations from phosphenium cations is not restricted to polyphosphines and P4 as substrates, but opens the way to polyphosphorus ligands fixed in the coordination sphere of transition metals.